2017
DOI: 10.1515/cclm-2017-0311
|View full text |Cite
|
Sign up to set email alerts
|

Differences in levels of albumin, ALT, AST, γ-GT and creatinine in frail, moderately healthy and healthy elderly individuals

Abstract: Because a group of people are at the same age, they should not be assessed the same way. To interpret results of laboratory tests in elderly is a complex task, where reference intervals are one part, but far from the only one, to take into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…Hypoalbuminemia is known to be more prevalent in elderly individuals who are frail compared with those who are healthy. In healthy elderly males, high CRP level and hypoalbuminemia increased the risk of early death (42). A higher GPS value was associated with elderly age in our study; however, elderly age and higher GPS values were independent predicting factors for mortality in patients with TB pleurisy.…”
Section: Discussioncontrasting
confidence: 50%
“…Hypoalbuminemia is known to be more prevalent in elderly individuals who are frail compared with those who are healthy. In healthy elderly males, high CRP level and hypoalbuminemia increased the risk of early death (42). A higher GPS value was associated with elderly age in our study; however, elderly age and higher GPS values were independent predicting factors for mortality in patients with TB pleurisy.…”
Section: Discussioncontrasting
confidence: 50%
“…ALT, ALB, TB, and γ -GT as liver markers were associated with a high risk of mortality [ 31 ] and metabolic syndrome-related diseases, such as cardiovascular diseases [ 32 ]. Edvardsson et al [ 33 ] measured the hepatic function indices of 596 healthy and frail older adult over 80 years of age; compared with healthy older individuals, frail older individuals had lower ALT but higher γ -GT. Xu [ 34 ] measured the serum ALT of 8 437 older residents aged 60 and above in Shanghai; the results showed that ALT decreased with age.…”
Section: Discussionmentioning
confidence: 99%
“…This condition identifies a subset of older people at high risk of progressing to frailty(75). Studies characterizing frailty conditions in this person's ability to perform ADLs, and cognitive function (tested using the Mini Mental State Examination (MMSE))(78). Some researchers emphasize the importance of history taking and clinical examination in identifying frailty(79) and…”
mentioning
confidence: 99%